A RARE CASE OF SUCCESSFUL STAGED SURGERY IN THE PATIENT WITH JOINED STENOSIS OF THE VERTEBRAL CANAL AT THE CERVICAL, THORACIC AND LUMBAR LEVELS - V. A. Byvaltsev; A. A. Kalinin; V. V. Shepelev; I. A. Stepanov (Инновационная медицина Кубани)
In the present article we describe a clinical example of a successful staged surgical treatment in the patient with rare joined stenosis of the vertebral canal at the cervical, thoracic and lumbar levels, surgical rehabilitation was 24 weeks. In connection with clinical data the first stage included ventral decompression of the cervical department of the spinal cord and spondylodesis by a telescopic prosthesis of a vertebral body, during the second stage through a minithoracotomy with an endovideo-assistance we performed anterolateral decompression of the spinal cord and spondylodesis by a telescopic prosthesis of a vertebral body with a lateral plate, and the third stage consisted of dorsal decompression of a dural bag and roots of the spinal cord, transpedicular fixation with an interbody spondylodesis in a lumbar department of the spine. Applying low-traumatic techniques for decompression and spondylodesis with specialized devices we could decrease level of pain syndrome, degree of neurologic deficiency, improve life quality and carry out effective fixation of three operated on vertebral aspects. Mini-invasive staged microsurgical decompressive stabilizing techniques can be used for successful treatment in patients with joined stenoses in the vertebral canal and also allow to reduce considerable risks for life and to cause full rehabilitation in the shortest possible time.